2013
DOI: 10.1111/vox.12072
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of buffy‐coat‐derived leucodepleted platelet concentrates in PAS‐plasma, prepared by the OrbiSac or TACSI automated system

Abstract: The systems OrbiSac and TACSI can be used to produce buffy-coat-derived PCs whose cell content, platelet function and metabolism are similar during standard storage. However, the preparation with the OrbiSac system induces a transient increase in platelet activation and release of proinflammatory substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Two published studies compared platelet characteristics of PCs obtained with TACSI and OrbiSac systems . First, Sandgren et al .…”
Section: Automation Second Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two published studies compared platelet characteristics of PCs obtained with TACSI and OrbiSac systems . First, Sandgren et al .…”
Section: Automation Second Generationmentioning
confidence: 99%
“…Second, Plaza et al . performed a two‐paired study because authors pooled 10 ABO‐matched BCs with PAS and split it into two identical aliquots One aliquot was used to prepare PCs with the TACSI system, and the other aliquot was used to prepare PCs with the OrbiSac system. Regarding qualitative results, Plaza et al .…”
Section: Automation Second Generationmentioning
confidence: 99%
“…Sandgren et al found no significant differences in platelet counts, lactate dehydrogenase (LDH), mean platelet volume (MPV) and adenosine triphosphate (ATP) between groups, and they concluded that PCs prepared by the TACSI system were equivalent to PCs prepared by the OrbiSac system with regard to in vitro characteristics during 7 days of storage. Second, Plaza et al [21] performed a two-paired study because authors pooled 10 ABOmatched BCs with PAS and split it into two identical aliquots. One aliquot was used to prepare PCs with the TACSI system, and the other aliquot was used to prepare PCs with the OrbiSac system.…”
Section: Tacsi Systemmentioning
confidence: 99%
“…© 2015 International Society of Blood Transfusion, ISBT Science Series (2016) 11 (Suppl. 1),[19][20][21][22][23][24][25] Optimizing WB processing 21…”
mentioning
confidence: 99%
“…Equipment developed to perform a first run for the separation of WB collected in a specific ‘top‐and‐bottom’ collection set and a second run for the separation of pooled BCs into PC. However, there are published papers on the use of the TACSI PL for pooled BC platelets concentrates production . The quality of the components is evaluated in accordance with EU quality requirements.…”
Section: Introductionmentioning
confidence: 99%